2019
DOI: 10.1111/bph.14688
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of oligomeric amyloid β peptide binding to α7 nicotinic receptor

Abstract: Background and Purpose Progressive dysfunction of cholinergic transmission is a well‐known characteristic of Alzheimer's disease (AD). Amyloid β (Aβ) peptide oligomers are known to play a central role in AD and are suggested to impair the function of the cholinergic nicotinic ACh receptor α7 (α7nAChR). However, the mechanism underlying the effect of Aβ on α7nAChR function is not fully understood, limiting the therapeutic exploration of this observation in AD. Here, we aimed to detect and characterize Aβ bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Aβos have high affinity with α7nAChR [ 50 ], and lead to the internalization of the Aβ–α7nAChR complex, which induces plaque formation and promotes neurotoxicity [ 51 , 52 ]. However, some studies have found that α7nAChR had a neuroprotective effect.…”
Section: The Neurotoxicological Mechanisms Of Aβosmentioning
confidence: 99%
“…Aβos have high affinity with α7nAChR [ 50 ], and lead to the internalization of the Aβ–α7nAChR complex, which induces plaque formation and promotes neurotoxicity [ 51 , 52 ]. However, some studies have found that α7nAChR had a neuroprotective effect.…”
Section: The Neurotoxicological Mechanisms Of Aβosmentioning
confidence: 99%
“…Recently, FRET has been used to identify the binding of A β oligomers to the cholinergic nicotinic ACh receptor α 7 ( α 7nAChR) (Cecon et al ., 2019). Loss of activity of α 7nAChR is believed to impair cognitive performance in AD (Bertrand et al ., 2015).…”
Section: Smts For Biophysical Studies Of Amyloid Proteinsmentioning
confidence: 99%
“…The result showed that the A β binding site on α 7nAChR overlaps with the orthosteric ligand binding sites comprising loop C with a high-binding affinity (p K D 10.3 ± 0.2). FRET was also used to evaluate different α 7nAChR-related compounds of interfering with the binding abilities of A β to α 7nAChR (Cecon et al ., 2019). In addition, FRET was applied for the screening of various compounds against Zn 2+ –A β interaction (Lee et al ., 2019).…”
Section: Smts For Biophysical Studies Of Amyloid Proteinsmentioning
confidence: 99%
“…Even though strategies to elevate expression or activity of these mechanisms still heavily rely on the amyloid cascade hypothesis, they do provide alternative therapeutic opportunities in dementia and relate to the overall increased interest in proteostatic clearance pathways that are further mentioned below. Better preclinically characterized tool compounds that modulate cellular Aβ and APP levels may also assist researchers such as Lopez Sanchez, van Wijngaarden, and Trounce () and Cecon et al (), providing insights into whether it is the loss of protective non‐amyloidogenic APP fragments or a gain of Aβ toxic function that is more detrimental in AD. Cellular location also appears to be an important factor in pathogenesis—the link between APP or APP‐derived peptides and mitochondrial metabolism remains unclear, despite the mitochondria being a location for APP and Aβ, and energy deficiency a recognized early event in AD progression (Lopez Sanchez et al, ).…”
Section: Progress On Recognized Therapeutic Targetsmentioning
confidence: 99%
“…Continued identification and characterization of binding partners for APP and Aβ also increase the appreciation of the complexity in the pathways related to APP metabolism and their involvement in disease. There are various species of Aβ that are known to act as ligands to neurotransmitter receptors in the brain, and Cecon et al () highlight the α7 nicotinic receptor (α7nAChR) as one of these binding partners. As a receptor involved in learning and memory processes, the function of α7nAChR is altered in the course of AD pathology (Bertrand, Lee, Flood, Marger, & Donnelly‐Roberts, ) and provides the basis of a sensitive Aβ screening assay for identifying inhibitors that will specifically target a detrimental effect of oligomeric Aβ accumulation (Cecon et al, ).…”
Section: Progress On Recognized Therapeutic Targetsmentioning
confidence: 99%